2022
DOI: 10.3389/fpubh.2022.958668
|View full text |Cite
|
Sign up to set email alerts
|

Perception towards vaccine effectiveness in controlling COVID-19 spread in rural and urban communities: A global survey

Abstract: IntroductionSeveral studies exhibited varying reports of perception toward vaccine effectiveness, vaccine hesitancy, and acceptance of COVID-19 vaccines. As this fluctuated with evidence generation, this study explored the perception toward vaccine effectiveness in rural and urban communities among various countries.MethodsA cross-sectional study was conducted online from April to August 2021 using convenience sampling among people from different countries approved by the Asia Metropolitan University Medical R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…On the other hand, a higher number of vaccinated individuals reported trust in healthcare workers, scientific research, and pharmaceutical companies. These findings confirmed that vaccine acceptance involves trusting the providers (e.g., specific healthcare professionals and doctors) and policymakers (e.g., the health system and public researchers) [ 13 , 34 , 50 ]. Additionally, unvaccinated individuals reported that mass media and newspapers fueled their doubts about vaccination.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, a higher number of vaccinated individuals reported trust in healthcare workers, scientific research, and pharmaceutical companies. These findings confirmed that vaccine acceptance involves trusting the providers (e.g., specific healthcare professionals and doctors) and policymakers (e.g., the health system and public researchers) [ 13 , 34 , 50 ]. Additionally, unvaccinated individuals reported that mass media and newspapers fueled their doubts about vaccination.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, qualitatively investigating which factors contribute to vaccine hesitancy can assist in the planning of tailored communication campaigns and fighting public health threats. To date, most qualitative studies in the scientific literature have investigated opinions about vaccines through semi-structured interviews with open-ended responses or content analysis posted on social media [ 18 , 19 , 32 , 33 , 34 , 35 ]. Conversely, there is a paucity of qualitative research on free associations related to the vaccine topic provided by vaccinated versus unvaccinated people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to various sources that hold information about vaccines, especially those providing inaccurate information, affects decision-making [ 56 ]. Some scholars have concluded that people’s perceptions of vaccine acceptance were influenced by the flow of information on various social media platforms and by the severity of COVID-19 cases [ 3 ]. A study in this context found that the more the participants were exposed to statements about the severity of post-COVID-19 vaccine side effects on social media, the more severe their own post-vaccination side effects were [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, two-thirds of the participants agreed that a vaccine effectively controlled viral spread. At the same time, one-quarter believed they did not need the vaccine if the others were vaccinated [ 3 ].…”
Section: Introductionmentioning
confidence: 99%